MISPRONUNCIATION OF ENGLISH CONSONANT SOUND [θ] IN THE MEDIAL POSITION BY THE STUDENTS OF SMK GRAFIKA SURAKARTA - Agatha Christie Yuansa Aji; Nurul Alfiani; Ayum Andar Sasmita (Magister Scientiae, 2020)
In this research, the researcher analyzes the mispronunciation of consonant [θ] in the middle of the word by the students of SMK Grafika Surakarta. In this research, there are two problems that will be discussed. The first is to find out the consonants that appear replacing consonant [θ] in these mispronunciations. The second one is to analyze the reasons behind the appearance of those consonants. Based on the data analysis, there are 194 mispronunciations of English consonant [θ] from 195 pronunciations (15 participants x 13 English words). From the analysis, there are seven consonants that appear replacing consonant [θ]. They are consonants [t], [r], [s], [tʃ], [f], [h], and [ð]. There are some reasons behind those consonants’ appearance. Firstly, those consonants have some closest segments with consonant [θ]. Secondly, those are affected by the pronunciation of the words that the students are familiar with and also that have similar patterns in English words alphabetically. For example, is the word ‘method’ [meθəd] and metode [metɑde].Another reason behind these mispronunciations is seen through their mother tongue, Javanese. In fact, consonant [θ] does not exist in Javanese consonants. Hence, the students are pronouncing the consonants that they are familiar with to make it easy to be spoken and easy to be understood by the listeners.